The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1016/s0014-5793(99)01230-2
|View full text |Cite
|
Sign up to set email alerts
|

Function of the second nucleotide‐binding fold in the CFTR chloride channel

Abstract: To test the role of nucleotide-binding fold (NBF) 2 and its interaction with the regulatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(74 reference statements)
1
8
0
Order By: Relevance
“…It has been found, however, that the number of amino acids deleted in NBD2 and their locations can greatly influence maturation and activity of the protein. For example, a ⌬NBD2 CFTR mutant lacking amino acids 1185 to 1349 did not mature in HEK 293 cells (Zerhusen and Ma, 1999). Channel measurements on microsomal membranes, however, showed that the mutant was active.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found, however, that the number of amino acids deleted in NBD2 and their locations can greatly influence maturation and activity of the protein. For example, a ⌬NBD2 CFTR mutant lacking amino acids 1185 to 1349 did not mature in HEK 293 cells (Zerhusen and Ma, 1999). Channel measurements on microsomal membranes, however, showed that the mutant was active.…”
Section: Discussionmentioning
confidence: 99%
“…The TMDs contribute to the formation of the Cl À selective pore [18,[45][46][47][48][49][50], the NBDs bind and hydrolyze ATP to regulate channel gating [19,21,[51][52][53] and phosphorylation of the R domain controls channel activity [54][55][56][57][58]. Zerhusen and Ma [59] suggested that NBD2 could have inhibitory and stimulatory roles in CFTR activity by interaction with NBD1 directly or indirectly via the R domain.…”
Section: Walker Motifsmentioning
confidence: 99%
“…The predicted location of all 18 endogenous cysteines is depicted [1,[21][22][23][24]. filtered at 100 Hz, digitized at 1 kHz, and analyzed as above.…”
Section: Fig 2 Cftr Topologymentioning
confidence: 99%